Single Nucleotide Polymorphism Markers for Genetic Mapping in Drosophila melanogaster - Hoskins, Roger A.; Phan, Alexander C.; Naeemuddin, Mohammed; Mapa, Felipa A.; Ruddy, David A.; Ryan, Jessica J.; Young, Lynn M.; Wells, Trent; Kopczynski, Casey; Ellis, Michael C. (Genome Research, 2001)
For nearly a century, genetic analysis in Drosophila melanogaster has been a powerful tool for analyzing gene function, yet Drosophila lacks the molecular genetic mapping tools that recently have revolutionized human, mouse, and plant genetics. Here, we describe the systematic characterization of a dense set of molecular markers in Drosophila by using a sequence tagged site-based physical map of the genome. We identify 474 biallelic markers in standard laboratory strains of Drosophila that span the genome. Most of these markers are single nucleotide polymorphisms and sequences for these variants are provided in an accessible format. The average density of the new markers is one per 225 kb on the autosomes and one per megabase on the X chromosome. We include in this survey a set of P-element strains that provide additional use for high-resolution mapping. We show one application of the new markers in a simple set of crosses to map a mutation in the hedgehog gene to an interval of <1 Mb. This new map resource significantly increases the efficiency and resolution of recombination mapping and will be of immediate value to the Drosophila research community.